Extending beyond Policy: Reaching UNAIDS’ Three “90”s in Malawi - Chirwa, Zengani; Kayambo, Florence; Oseni, Lolade; Plotkin, Marya; Hiner, Cyndi; Chitsulo, Chimwemwe; Curran, Kelly; Kalua, Thokozani; Stender, Stacie C. (Frontiers in Public Health, 2018)
• Malawi, like other countries with a generalized HIV epidemic, is striving to reach the ambitious targets set by UNAIDS known as the Three 90’s for testing, provision of antiretroviral therapy and viral suppression. • Assisted by Malawi’s progressive policies on HIV/AIDS, it appears possible that Malawi will attain these goals, but only by employing innovative program approaches to service delivery which help fill policy gaps. • This article describes how a dedicated cadre of lay-person testers and HIV-positive peers appears to have helped attain increases in HIV and viral load testing and retention in care in four districts in Malawi, and situates these innovations in a policy framework analysis.